Solidarity without conditionality: Comparing the EU Covid-19 safety nets SURE, pandemic Crisis Support, and European Guarantee Fund - Vincent Lindner (Leibniz Institute for Financial Research SAFE, 2022)
This article compares the three initial safety nets spanned by the European Union in response to the Covid-19 crisis: SURE, the Pandemic Crisis Support, and the European Guarantee Fund. It compares their design regarding scope, generosity, target groups, implementation, the types of solidarity and conditionality, and asks how they reflect on core-periphery relations in the EU. The article finds that the most important factor in all three instruments is risk-sharing between member states, even though SURE and the EGF display elements of fiscal solidarity. Finally, the article shows that Euro crisis countries from the South are the main recipients of financial aid, while Central and East European countries receive significantly less assistance and core countries in the North and West have no need for them.
urn:nbn:de:hebis:30:3-619980
Keywords: 330; financial solidarity; conditionality; Covid-19; European Commission; European Stability Mechanism; European Investment Bank